Placental fissure in mongrel cats, Felis catus - Linnaeus, 1758: gross and microscopical aspects - Ambrósio, Carlos Eduardo; Miglino, Maria Angélica; Lima, Ana Rita; Martins, Daniele dos Santos; Assis-Neto, Antonio Chaves; Bonatelli, Marina; Verechia, Flávia Thomaz; Carvalho, Ana Flávia de (Brazilian Journal of Veterinary Research and Animal Science, 2004)
This research consists of study of shematic macroscopy cat's placenta and placental characterization as its type, zonary placenta, that 62,5% of cases presents a fissure at distal area of umbilical cord. This is formed by a joustfetal area, joustplacental area and middle area, histological findings: two arteries, a vein, two vitelline pedicule and two allantois pedicule. In the fissure, an allantoic epithelium covering this area at 10% of the cases and 90% found a trophoblast decrease compared with others placental areas out of the fissure. So, the feline placenta, in its maternal/fetal relationship shows a imcomplete zonary placenta, different of that occurs in other carnivores.